Trocas gasosas, tolerância protoplasmática e anatomia do lenho em Handroanthus spp. (Bignoniaceae) em condições de déficit hídrico - Cliciana Hollanda Cavalcanti de Sá (2017)
Belo Horizonte, MG, is known as “garden city” due to the number of gardens and green areas and is also a city which contain many ipês. Most of its species are yellow and purple followed by the white ipê, all belonging to the genus Handroanthus (Bignoniaceae). Specific laws state that the use and maintenance of trees in urban areas should take into consideration different aspects of growth and physiology, and therefore allow its several uses and social environmental services to be reached. Contrastingly, very little is known about the environmental stresses on these trees, such as impermeability and soil compaction, the increase of the average air temperature, the changes of atmospheric gases and pollution, and the lack and excess of light and water. These factors, together or separately, pose significant growth and plant development constraints. In this sense, the purpose of this study was to evaluate the effects of drought on leaves and stems of three Handroanthus species cultivated in greenhouse conditions. Plants were cultivated in different hydric soil conditions for the evaluation of leaf gas exchange and leaf tissue integrity through electrolyte releasing ex vivo and the anatomy of secondary xylem in stems. The results from the leaf gas exchange showed that the Handroanthus chrysotrichus had the most tolerance to water stress, even though the Handroanthus impetiginosus and Handroanthus roseoalbus were significantly tolerant to drought. In evaluating the leaf tissue integrity, the H. roseoalbus and H. impetiginosus were more tolerant to electrolyte releasing when compared to the lowest hydric potential values, to which they were submitted. This behavior reflected less membrane damage for this species in comparison to the greatest membrane damage in H. chrysotrichus. When analyzing the secondary xylem anatomy, all three species presented traits of tolerance to water deficit. Both H. chrysotrichus and H. impetiginosus had striking characteristics such as dense fibers, abundant axial parenchyma and starch storage in parenchyma cells, being similar to each other, and differing to H. roseoalbus. In this case, the least and most dense fibers were observed, reduced axial parenchyma and starch storage, and therefore becoming the most sensitive species to water deficit between the three. The results of this study have assisted in the selection of which species of ipês should be used for urban forestation when evaluating climate changes and may assist in managing the seedlings to be planted as well as considering the most appropriate substitutions.